Structural and functional evidence that a B chromosome in the characid fish Astyanax scabripinnis is an isochromosome - Mestriner, C. A. (2000)
Astyanax scabripinnis possesses a widespread polymorphism for metacentric B chromosomes as large as the largest chromosome pair in the A complement. on the basis of C-banding pattern, it was hypothesized that these B chromosomes are isochromosomes that have arisen by means of centromere misdivision and chromatid nondisjunction. In the present paper we test this hypothesis by analysing (i) the localization of a repetitive DNA sequence on both B chromosome arms, and (ii) synaptonemal complex formation, in order to test the functional homology of both arms. Genomic DNA digested with KpnI and analysed by gel electrophoresis showed fragments in a ladder-like pattern typical of tandemly repetitive DNA. These fragments were cloned and their tandem organization in the genome was confirmed. A 51-bp long consensus sequence, which was AT-rich (59%) and contained a variable region and two imperfect reverse sequences, was obtained. Fluorescence in situ hybridization (FISH) localized this repetitive DNA into noncentromeric constitutive heterochromatin which encompasses the terminal region of some acrocentric chromosomes, the NOR region, and interstitial polymorphic heterochromatin in chromosome 24. Most remarkably, tandem repeats were almost symmetrically placed in the two arms of the B chromosome, with the exception of two additional small clusters proximally located on the slightly longer arm. Synaptonemal complex (SC) analysis showed 26 completely paired SCs in males with 1B. The ring configuration of the B univalent persisting until metaphase I suggests that the two arms formed chiasmata. All these data provided strong support for the hypothesis that the B chromosome is an isochromosome.